2017
DOI: 10.1055/s-0037-1606617
|View full text |Cite
|
Sign up to set email alerts
|

Do Knee Bracing and Delayed Weight Bearing Affect Mid-Term Functional Outcome after Anterior Cruciate Ligament Reconstruction?

Abstract: Purpose  The aim of this study was to assess the effect of knee bracing and timing of full weight bearing after anterior cruciate ligament reconstruction (ACLR) on functional outcomes at mid-term follow-up. Methods  We performed a retrospective study on 41 patients with ACLR. Patients were divided in two groups: ACLR group, who received isolated ACL reconstruction and ACLR-OI group who received ACL reconstruction and adjunctive surgery. Information about age at surgery, bracing, full or progressive weight bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Bracing and delayed weightbearing after isolated ACLR has been shown to decrease functional outcomes, based on IKDC scores, 21 but how this affects ACLR in conjunction with meniscal treatment has not been evaluated. Although there appeared to be some functional benefit to early motion and early weightbearing or some detriment to limitation at the midterm for isolated ACLR, our study found this did not hold true with concomitant meniscal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bracing and delayed weightbearing after isolated ACLR has been shown to decrease functional outcomes, based on IKDC scores, 21 but how this affects ACLR in conjunction with meniscal treatment has not been evaluated. Although there appeared to be some functional benefit to early motion and early weightbearing or some detriment to limitation at the midterm for isolated ACLR, our study found this did not hold true with concomitant meniscal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative knee bracing after ACLR has been shown to be associated with some additional adverse effects to the operated knee. Di Miceli et al [ 43 ] . showed that the use of a brace and delayed weight bearing after ACLR have a negative impact on long-term functional outcomes, according to the subjective IKDC score.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 911 studies were eligible (Fig. 1), but only 9 studies qualified for inclusion (1,8,(11)(12)(13)(14)(15)(16)(17) (Table I). Due to the considerable variation in rehabilitation protocols across studies, for the purposes of the current study accelerated weight-bearing was defined as full weight-bearing within 2 weeks, and delayed weightbearing was defined as full weight-bearing beyond 2 weeks.…”
Section: Study Selectionmentioning
confidence: 99%
“…The 9 studies reported IKDC scores (11)(12)(13)(14), with 2 studies excluded in the meta-analysis (15, 16) (mean and SD were not provided). One study reported that the accelerated weight-bearing group showed a better score (12).…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation